2021
DOI: 10.1136/practneurol-2020-002782
|View full text |Cite
|
Sign up to set email alerts
|

Trigeminal neuralgia: a practical guide

Abstract: Trigeminal neuralgia (TN) is a highly disabling disorder characterised by very severe, brief and electric shock like recurrent episodes of facial pain. New diagnostic criteria, which subclassify TN on the basis of presence of trigeminal neurovascular conflict or an underlying neurological disorder, should be used as they allow better characterisation of patients and help in decision-making regarding medical and surgical treatments. MR, including high-resolution trigeminal sequences, should be performed as part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
111
0
33

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(147 citation statements)
references
References 40 publications
3
111
0
33
Order By: Relevance
“…In our study, the impact of osteoporosis on the risk of TN increased differently in the two genders and was more prominent in the patients aged between 50–60 years. In addition, women and the elderly had a relative higher incidence of TN, which is consistent with a previous article [ 23 ]. Regardless of whether comorbidity co-existed or not, osteoporotic patients had a higher TN risk than non-osteoporosis patients.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, the impact of osteoporosis on the risk of TN increased differently in the two genders and was more prominent in the patients aged between 50–60 years. In addition, women and the elderly had a relative higher incidence of TN, which is consistent with a previous article [ 23 ]. Regardless of whether comorbidity co-existed or not, osteoporotic patients had a higher TN risk than non-osteoporosis patients.…”
Section: Discussionsupporting
confidence: 92%
“…Only a small percentage of TN patients present with demonstrable compression or morphological changes in the trigeminal nerve, and neurovascular compression does not always translate to disease [ 27 , 148 , 149 ]. Furthermore, most patients present with a normal physical and neurological exam, and there is a lack of reliable biomarkers for the disease [ 14 , 55 , 150 , 151 ]. Thus, such complex disease presentation makes accurate diagnosis of TN difficult for some patients and may even challenge the utility of the current classification scheme [ 152 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conventionally, procedural interventions will be offered when medical therapies fail, but there is little data to guide decisions on the timing of this decision. Even though, based on a few studies, surgical and minimally invasive interventions appear to have a promising track record in providing relief, they are also known to accompany a varying degree of complications and recurrence [ 151 ].…”
Section: Discussionmentioning
confidence: 99%
“…Trigeminal neuralgia (TN) is recurrent, unilateral, transient, and electric pain in the trigeminal nerve distribution area. It has been reported that the annual incidence is about 4–29/10 million person-years worldwide ( 1 ). The prevalence rate in women was higher than that in men (F:M = 3:2).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence rate in women was higher than that in men (F:M = 3:2). With disease aggravation, pain attacks become more frequent, affecting basic human functions, such as speaking, eating, drinking, or touching the face, resulting in low quality of life ( 1 ).…”
Section: Introductionmentioning
confidence: 99%